2015
DOI: 10.1371/journal.pone.0135650
|View full text |Cite
|
Sign up to set email alerts
|

Household Storage of Medicines and Associated Factors in Tigray Region, Northern Ethiopia

Abstract: IntroductionThe presence of medicines in households is a risk factor for irrational drug use. This study aimed at investigating the prevalence and factors associated with home storage of medicines in Tigray Region, Ethiopia.MethodA community based cross-sectional study was conducted in April 2013 in Tigray Region, Ethiopia. A total of 1034 participants were enrolled in the study. A multi-stage sampling method was employed to select households. Data were collected with the help of a pre-tested structured questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
53
4
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 10 publications
17
53
4
9
Order By: Relevance
“…The drugs most commonly stored were analgesics 12 (54.54%) and antimicrobials 6 (27.28%). In consistence with this finding the study conducted in Tigray region, Northern Ethiopia showed that analgesic and antibiotics were the most commonly stored category of modern drugs 20 . Most of the respondents, 10(45.45%), said they store their drugs to treat similar ailments in the future.Storing and using antibiotics without medical consultation, can lead to inappropriate use and contribute to the emergence of antibiotic resistance 21 .…”
Section: Discussionsupporting
confidence: 60%
“…The drugs most commonly stored were analgesics 12 (54.54%) and antimicrobials 6 (27.28%). In consistence with this finding the study conducted in Tigray region, Northern Ethiopia showed that analgesic and antibiotics were the most commonly stored category of modern drugs 20 . Most of the respondents, 10(45.45%), said they store their drugs to treat similar ailments in the future.Storing and using antibiotics without medical consultation, can lead to inappropriate use and contribute to the emergence of antibiotic resistance 21 .…”
Section: Discussionsupporting
confidence: 60%
“…This encourages the malpractice of wrongful selfmedication or sharing of medicines among friends, families exposing the community to potential health hazards such as adverse drug reactions and the emergence of antimicrobial resistance leading to ineffective treatment, poor quality of healthcare and also wastage of pharmaceutical resources. [4,5] Storing unused medication at home is a hidden hazard. Most medicines deteriorate with time leading to changes in their chemical composition rendering them less effective or, in some cases, potentially harmful if expired.…”
mentioning
confidence: 99%
“…A study of household drug storage in North Ethiopia also revealed that households with a family member working in health facilities were more likely to have home drug storage (87). Drug storage was found to be more prevalent among urban residents compared to rural residents in that study.…”
Section: In-home Storagementioning
confidence: 58%
“…Antibiotics are the most common group of in-house storage drugs (74,87). One out of ten households in the United Kingdom had antimicrobial drugs available at home (88).…”
Section: In-home Storagementioning
confidence: 99%
See 1 more Smart Citation